Quartz fiber reinforced phenolic aerogel composite material with densified surface layer and preparation method of quartz fiber reinforced phenolic aerogel composite material

Through the design of densified surface layer and light inner layer, combined with quartz fiber-reinforced phenolic aerogel composite material, the lack of performance of fiber-reinforced phenolic aerogel composite material in the prior art under a single-sided pneumatic heating environment is solved, and the performance of fiber-reinforced phenolic aerogel composite material in the prior art is achieved. It has comprehensive performance requirements for high-speed aircraft and has excellent ablation, heat insulation and impact resistance.

CN119116478AActive Publication Date: 2024-12-13WUHAN UNIV OF TECH

Patent Information

Application Number
CN202411255464.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-09
Publication Date
2024-12-13
Estimated Expiration
2044-09-09

AI Technical Summary

Technical Problem

The existing fiber-reinforced phenolic aerogel composites have insufficient ablation and impact resistance in a single-sided pneumatic heating environment, and the weight is high during the preparation process, making it difficult to meet the comprehensive performance needs of high-speed aircraft.

Method used

Using quartz fiber-reinforced phenolic aerogel composite material with densified surface and light inner layer, the polycarbosilane-modified bismaleimide resin is used as the densified surface matrix and the phenolic aerogel is used as the light inner layer matrix. Combining quartz fiber woven fabric and needle felt, the material is resistant to ablation, heat insulation and impact resistance using domain enhancement and overall connectivity design.

Benefits of technology

It realizes the improvement of the material's ablation, heat insulation and impact resistance under low quality cost, meets the use needs of high-speed aircraft, and improves the overall performance stability of the material through molecular-level combination and gradient heating and curing. and mechanical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005033913820000071
    Figure BDA0005033913820000071
  • Figure BDA0005033913820000081
    Figure BDA0005033913820000081
  • Figure BDA0005033913820000082
    Figure BDA0005033913820000082
Patent Text Reader

Abstract

The invention belongs to the technical field of thermal insulation materials, and discloses a quartz fiber reinforced phenolic aerogel composite material with a densified surface layer and a preparation method of the quartz fiber reinforced phenolic aerogel composite material. The composite material comprises a densified surface layer and a light inner layer, the densified surface layer takes polycarbosilane modified bismaleimide resin as a matrix and quartz fiber woven cloth as a reinforcement; and the light inner layer takes phenolic aerogel as a matrix and quartz fiber needled felt as a reinforcement body. The preparation method comprises the following steps: connecting the surface layer woven fabric and the inner layer needled felt into a whole through needling, and then sequentially filling the surface layer matrix and the inner layer matrix. The aerogel composite material has the characteristics of ablation resistance, tough surface and heat insulation, the comprehensive density and the comprehensive mechanical property can be regulated and controlled, and the comprehensive requirements of heat insulation, low-speed impact resistance, light weight and certain mechanical strength of a large-area thermal protection structure of the windward side of a hypersonic speed device on the phenolic aerogel composite material can be met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of heat-insulating materials, and in particular relates to a quartz fiber reinforced phenolic aerogel composite material with a densified surface layer and a preparation method thereof. Background Art

[0002] In recent years, as ultra-high-speed aircraft develop towards high-speed cruising, wide-range flight, horizontal take-off and landing, comprehensive performance requirements have been put forward for thermal protection materials and structures. Taking the large-area external heat protection structure on the windward side as an example, the heat-insulating materials used must not only be lightweight, ablation-resistant and highly heat-insulating, but also have the characteristics of sand impact resistance and high comprehensive mechanical properties. In addition, the cycle and cost of the preparation process of heat-insulating materials must also be considered.

[0003] Phenolic resin aerogel has the advantages of short preparation cycle and mass production. With the advantages of process and cost, phenolic aerogel is widely used in the field of thermal protection of aerospace vehicles as an ablative thermal protection material. However, with the changes in the service environment and working conditions of hypersonic aircraft, new thermal, mechanical and weight requirements are put forward for phenolic aerogel, a traditional thermal protection material. The use of flexible fiber felt or chopped fibers to reinforce phenolic aerogel can improve the strength and toughness of phenolic aerogel composites to a certain extent. However, this method does not target the characteristics of one-sided aerodynamic heating in the application environment. The prepared fiber-reinforced phenolic aerogel composite material belongs to a homogeneous structure, and there are still deficiencies in ablation resistance and impact resistance, which cannot meet the needs of high-speed aircraft for new thermal insulation materials.

[0004] In recent years, researchers have used inorganic particle-modified resin and quartz fiber as the surface dense layer to improve the ablation resistance of phenolic aerogel composites. However, the surface dense layer prepared by this method has a significant weight gain, and while achieving ablation resistance, the phenolic aerogel composite material pays a high weight price. In addition, it is difficult for solid inorganic particles and liquid resin to achieve molecular level bonding, and the surface defects caused by particle agglomeration or uneven dispersion seriously affect the thermal insulation performance of the composite material. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a quartz fiber reinforced phenolic aerogel composite material with a densified surface layer and a preparation method thereof in view of the shortcomings of the prior art. Firstly, in view of the characteristics of single-sided aerodynamic heating, the fiber preform is designed and prepared with the idea of ​​localized reinforcement and overall connectivity. Secondly, for the fiber preforms in different areas, the dense surface matrix and the loose inner matrix are filled in sequence. The composite material finally prepared has good ablation resistance, thermal insulation performance and impact resistance, and the comprehensive density can be adjusted to meet the use requirements of hypersonic vehicles.

[0006] In order to solve the technical problem raised by the present invention, the present invention provides a quartz fiber reinforced phenolic aerogel composite material with a densified surface layer, comprising a densified surface layer and a lightweight inner layer; the densified surface layer uses polycarbosilane-modified bismaleimide resin as a matrix and quartz fiber woven fabric as a reinforcement; the lightweight inner layer uses phenolic aerogel as a matrix and quartz fiber needle felt as a reinforcement.

[0007] In the above scheme, the polycarbosilane-modified bismaleimide resin consists of bismaleimide resin, polycarbosilane and a silane coupling agent.

[0008] Furthermore, the polycarbosilane is liquid polycarbosilane, and its number average molecular weight is 1000-2000.

[0009] Furthermore, the solid content of the bismaleimide resin is 75-95%.

[0010] Furthermore, the silane coupling agent is γ-aminopropyltriethoxysilane (KH550).

[0011] Furthermore, in the polycarbosilane-modified bismaleimide resin, the mass ratio of bismaleimide resin, polycarbosilane, and silane coupling agent is 100:(5-35):(0.3-5).

[0012] In the above scheme, the quartz fiber woven fabric is a 2.5D woven fabric with a warp density of 11 to 13 yarns / cm, a weft density of 9 to 11 yarns / cm, and a thickness of 1 to 3 mm.

[0013] In the above scheme, the density of the quartz fiber needle felt is 0.2-0.5 g / cm 3 , thickness is 9~29mm.

[0014] In the above scheme, the volume density of the composite material is 0.3-0.7 g / cm 3 The room temperature thermal conductivity is 0.07-0.11 W / m·K, the bending strength is 9-13 MPa, and the hardness is 94-100 HA.

[0015] The present invention also provides a method for preparing a quartz fiber reinforced phenolic aerogel composite material having a densified surface layer, comprising the following steps:

[0016] 1) connecting the quartz fiber woven fabric and the quartz fiber needle felt by needle punching to form a connected fiber preform;

[0017] 2) Mix polycarbosilane and anhydrous ethanol and add them to bismaleimide resin, stir first and then disperse by ultrasonic, then add silane coupling agent, continue stirring and heating to accelerate the volatilization of anhydrous ethanol. A polycarbosilane-modified bismaleimide resin film is prepared by calendering method;

[0018] 3) Covering the surface of the quartz fiber woven fabric of the fiber preform with a polycarbosilane-modified bismaleimide resin film, then sealing it in a vacuum bag and evacuating it, heating it to melt-infiltrate the polycarbosilane-modified bismaleimide resin film into the quartz fiber woven fabric, then heating it to solidify it, taking it out, heat-treating it in an inert atmosphere, and cooling it to room temperature to obtain a fiber preform with a densified surface layer;

[0019] 4) mixing phenolic resin with anhydrous ethanol, heating to dissolve, and then adding hexamethylenetetramine to obtain a phenolic aerogel precursor solution;

[0020] 5) placing the fiber preform with a densified surface layer into a mold, transferring the phenolic aerogel precursor solution from the surface of the quartz fiber needle felt of the fiber preform inward through a resin transfer molding process, so that the phenolic aerogel precursor solution infiltrates the quartz fiber needle felt, and then applying pressure into the mold, heating and heat preservation, demolding, taking out and drying, to obtain a quartz fiber reinforced phenolic aerogel composite material with a densified surface layer.

[0021] In the above scheme, the needle density of the needle connection is 25 to 35 needles / cm 2 .

[0022] In the above scheme, in step 2), the mass ratio of bismaleimide resin to anhydrous ethanol is 100:(10-30).

[0023] In the above scheme, in step 2), the stirring rate is 500-1000 r / min, the stirring time before the addition of the silane coupling agent is 10-20 min, and the stirring time after the addition of the silane coupling agent is 0.5-2 h.

[0024] In the above scheme, in step 2), the ultrasonic dispersion time is 5 to 20 minutes.

[0025] In the above scheme, in step 2), the heating temperature is 80-90° C. and the heating time is 2-4 hours, until the residual mass of anhydrous ethanol does not exceed 15% of the sum of the mass of polycarbosilane and bismaleimide resin.

[0026] In the above solution, the thickness of the polycarbosilane-modified bismaleimide resin film is the same as the thickness of the quartz fiber woven fabric.

[0027] In the above scheme, the vacuum degree of the vacuum bag after evacuation is 0.09-0.1 MPa.

[0028] In the above scheme, the melt infiltration temperature of the polycarbosilane-modified bismaleimide resin film is 140-150° C., and the film is kept at this temperature for 2-6 hours.

[0029] In the above scheme, in step 3), the curing adopts three-stage gradient temperature curing, the temperature of the first stage is 175-185°C, the temperature of the second stage is 205-215°C, the temperature of the third stage is 225-235°C, and the insulation time of each stage is 1-3h.

[0030] In the above scheme, the ventilation rate of the inert atmosphere is 20 to 50 ml / min.

[0031] In the above scheme, the temperature of the heat treatment is 900-1000° C., the heating rate is 2-10° C. / min, and the treatment time is 10-30 min.

[0032] In the above scheme, the phenolic resin is a linear phenolic resin, and its number average molecular weight is 300-800.

[0033] In the above scheme, in step 4), the heating temperature is 60-80° C. and the heating time is 0.5-2 h.

[0034] In the above scheme, in step 4), the mass ratio of phenolic resin, anhydrous ethanol and hexamethylenetetramine is 100:(10-60):(10-20).

[0035] In the above scheme, in step 5), an air compressor is used to inject a pressure of 0.3 to 0.5 MPa into the mold.

[0036] In the above scheme, in step 5), the heating temperature is 90-100° C. and the insulation time is 24-48 hours.

[0037] In the above scheme, in step 5), the drying is natural drying, and the drying time is 24 to 48 hours.

[0038] Compared with the prior art, the present invention has the following beneficial effects:

[0039] 1) The composite material of the present invention adopts a localized reinforcement design in view of the characteristics of single-sided start-up heating. First, the matrix adopts a localized reinforcement design, and liquid polycarbosilane and liquid bismaleimide resin are blended to fully combine at the molecular level to achieve densification at a low quality cost. The internal matrix adopts phenolic aerogel, and the porous and lightweight structure makes the material have better thermal insulation performance. The surface layer and the inner layer are connected by needle puncture to form an integrated fiber preform. Thereby having excellent comprehensive performance, it meets the use requirements of hypersonic vehicles.

[0040] 2) The composite material of the present invention uses polycarbosilane-modified bismaleimide resin as the matrix of the densified surface layer. First, compared with phenolic resin, bismaleimide resin does not produce small molecules during the curing process, making the surface denser and improving heat resistance; second, polycarbosilane-modified bismaleimide resin is used, and the cracking products generated after heat treatment can form a protective layer, reducing the thermal decomposition and mass loss of the material, and the thermal protective layer can block the transfer of heat to the inside of the material, improving the material's anti-ablation performance and thermal stability, so that the composite material can be used in a hot environment, with excellent ablation resistance and impact resistance; third, liquid and liquid blending is used to avoid the sedimentation of solid particles, achieve molecular level bonding, ensure the uniformity of dispersion, and further adopt a stirring-ultrasound-stirring preparation process, and the final composite material has more stable properties; fourth, infiltration is carried out in the temperature range where the resin viscosity is the smallest, and the temperature is increased gradually during curing to avoid the sudden increase in curing temperature to produce thermal stress, so that the infiltration is more uniform and the degree of curing is higher, so that the mechanical properties of the material are better.

[0041] 3) The composite material of the present invention uses a fiber preform as a skeleton. The surface layer adopts a high-toughness 2.5D quartz fiber woven cloth to further strengthen the toughness and surface hardness of the surface layer. The internal reinforcement adopts quartz fiber felt to ensure the thermal insulation performance while increasing the strength and toughness of the phenolic aerogel. The dense surface layer and the lightweight inner layer are connected by a needle-punched structure, so that the dense surface layer and the lightweight inner layer are not easy to fall off, thereby ensuring the integrity of the composite material. The overall molding process of the composite material is simple and the preparation cycle is short. It can meet the needs of large-area external heat protection structure on the windward side of ultra-high-speed aircraft. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 This is a physical picture of the composite material obtained in Example 1.

[0043] Figure 2 This is a scanning electron microscope image of the composite material obtained in Example 1.

[0044] Figure 3 This is a background temperature curve of the composite material obtained in Example 1 subjected to a butane flame ablation test.

[0045] Figure 4 This is a state diagram of the composite material obtained in Example 1 after being subjected to a low-speed impact test and subjected to an impact energy of 23J.

[0046] Figure 5 This is a state diagram of the composite material obtained in Comparative Example 1 after being subjected to a low-speed impact test and subjected to an impact energy of 18J.

[0047] Figure 6 This is a background temperature curve of the composite material obtained in Comparative Example 2 subjected to a butane flame ablation test. DETAILED DESCRIPTION

[0048] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with the embodiments, but the content of the present invention is not limited to the following embodiments.

[0049] In the following examples, the polycarbosilane used is liquid polycarbosilane, which is sourced from Shandong Zibo Qiquan Industry and Trade Co., Ltd. and has a number average molecular weight M n 1000~1600; bismaleimide resin is N,N'-m-phenylene bismaleimide, which comes from Tianjin Qingkuai Technology Co., Ltd., and its weight average molecular weight M w The molecular weight of the phenolic resin is 400-1000, and the solid content is 95%; the silane coupling agent is γ-aminopropyltriethoxysilane (KH550); the phenolic resin is a solid linear phenolic resin, which is from Henan Hengyuan New Materials Co., Ltd., and the number average molecular weight is M n It is 300 to 800.

[0050] Example 1

[0051] A quartz fiber reinforced phenolic aerogel composite material with a densified surface layer comprises a densified surface layer and a lightweight inner layer; the densified surface layer uses polycarbosilane modified bismaleimide resin as a matrix and quartz fiber woven fabric as a reinforcement; the lightweight inner layer uses phenolic aerogel as a matrix and quartz fiber needle felt as a reinforcement.

[0052] Among them: the polycarbosilane modified bismaleimide resin is composed of bismaleimide resin, polycarbosilane and silane coupling agent in a mass ratio of 100:30:5; the quartz fiber woven fabric is a 2.5D woven fabric with a warp density of 12±0.5 strands / cm, a weft density of 10±0.4 strands / cm, and a thickness of 2mm; the density of the quartz fiber needle felt is 0.5g / cm 3 , thickness is 28mm.

[0053] The method for preparing the composite material comprises the following steps:

[0054] 1) Connect the quartz fiber woven fabric and the quartz fiber needle felt by needle punching, and the needle punching density is 30 needles / cm 2 , forming a connected fiber preform;

[0055] 2) Mixing polycarbosilane with anhydrous ethanol and adding the mixture to bismaleimide resin, wherein the mass ratio of bismaleimide resin to anhydrous ethanol is 100:30, stirring at a rate of 800 r / min for 10 min, and then ultrasonically dispersing the mixture for 15 min, then adding a silane coupling agent, stirring at a rate of 800 r / min for 0.5 h, and then heating to 80° C. and keeping the mixture for 2 h to accelerate the volatilization of ethanol, so that the residual mass of anhydrous ethanol does not exceed 15% of the sum of the mass of polycarbosilane and bismaleimide resin, and then preparing a polycarbosilane-modified bismaleimide resin film with a thickness of 2 mm by a calendering method;

[0056] 3) Covering the surface of the quartz fiber woven fabric of the fiber preform with a polycarbosilane-modified bismaleimide resin film, then placing it in a vacuum bag and evacuating it, closing the vacuum valve and sealing it after the vacuum degree reaches 0.1 MPa, placing it in an oven, heating it to 140°C in the oven and keeping it warm for 2 hours to make the polycarbosilane-modified bismaleimide resin film melt-infiltrate into the quartz fiber woven fabric, and then using a three-stage gradient temperature rise curing method, the three-stage temperatures are 180°C, 210°C, and 230°C, respectively, and the insulation time for each stage is 2 hours. After the curing is completed, take it out, put it into a tubular atmosphere furnace, pass nitrogen (ventilation rate is 30 ml / min), and heat it to 1000°C at a rate of 5°C / min for 10 minutes to obtain a fiber preform with a densified surface layer;

[0057] 4) mixing phenolic resin with anhydrous ethanol, heating to 80° C. to dissolve for 0.5 h, and then adding hexamethylenetetramine to obtain a phenolic aerogel precursor solution; wherein the mass ratio of the linear phenolic resin, anhydrous ethanol, and hexamethylenetetramine is 100:25:10;

[0058] 5) placing the fiber preform with a densified surface layer into a mold, transferring the phenolic aerogel precursor solution from the surface of the quartz fiber needle felt of the fiber preform inward through a resin transfer molding process, so that the phenolic aerogel precursor solution infiltrates the quartz fiber needle felt, and then using an air compressor to pressurize the mold with a pressure of 0.4 MPa. After the pressing is completed, heating to 90° C. and keeping warm for 24 hours, demolding, taking out and drying naturally for 24 hours, to obtain a quartz fiber reinforced phenolic aerogel composite material with a densified surface layer.

[0059] The properties of the composite material prepared in this example were tested, including:

[0060] 1) Density determination: the bulk density is determined according to the standard GB / T 2998-2015. The product size is 100.1mm×100.3mm×29.8mm. Before the test, the product is dried in an oven at 110℃±5℃, and then cooled to room temperature in a desiccator. Repeat the test five times and take the average value;

[0061] 2) Thermal conductivity determination: The room temperature thermal conductivity is determined according to standard YB / T 4130-2005. The product size is 100.1mm×100.3mm×29.8mm. Repeat the test five times and take the average value;

[0062] 3) Butane flame ablation test: the test sample size is a cylindrical specimen of φ40mm×30mm. The densified surface of the specimen is ablated for 500s. An infrared temperature gun and a thermocouple are used to record the temperature of the front (densified surface) and back of the composite material during the ablation process. The thickness and mass before and after ablation are tested, and the ablation rate is calculated.

[0063] 4) Low-speed impact test: the test sample is a cubic specimen with a size of 100mm×100mm×10mm. A drop hammer tester is used to select hammers of various weight specifications ranging from 100g to 2kg. Free fall tests are carried out at different heights. The test is carried out in a manner of increasing the drop hammer energy in sequence, and the state of the specimen after impact is observed;

[0064] 5) Bending test: in accordance with standard GB / T1449, the test sample size is 80mm×15mm×4mm cubic spline with dense surface layer, and the test is carried out using an electronic universal testing machine with a loading rate of 1mm / min. The test is repeated four times to obtain the average value;

[0065] 6) Hardness test: According to standard ASTM D2240, the sample size is 100 mm × 100 mm × 30 mm. A Shore hardness tester is used to select five locations on the surface of the sample for hardness testing and take the average value.

[0066] Table 1 Performance test results of the composite material obtained in Example 1

[0067]

[0068] Combining Table 1 and Figures 1 to 4 The properties of the composite material prepared in this example are analyzed:

[0069] Figure 1 The composite material obtained in this example is shown in the figure. It can be seen from the figure that the composite material has a complete appearance without defects, and the densified surface layer is tightly connected to the lightweight inner layer. After testing, its density is 0.624g / cm 3 , and the thermal conductivity is 0.1049W / m·K, indicating that it has light weight and heat insulation properties.

[0070] Figure 2 This is a scanning electron microscope image of the composite material obtained in this embodiment. It can be seen from the figure that the fibers and resin in the densified surface layer and the lightweight inner layer are well bonded, and the bonding interface of the two layers is in good contact and tightly linked, with good integrity and is not easy to fall off during use.

[0071] Figure 3 The back temperature curve of the composite material obtained in this embodiment is subjected to a butane flame ablation test. It can be seen from the figure that after 500s of butane flame heating, the surface temperature of the composite material is relatively high, but the back temperature has always been at a low level, and the rate of increase is relatively low, showing excellent thermal insulation performance; at the same time, the linear ablation rate and mass ablation rate in Table 1 are both at a low level, indicating that the composite material has good ablation resistance.

[0072] Figure 4 This is a state diagram of the composite material obtained in this embodiment after being subjected to a low-speed impact test and subjected to an impact energy of 23J. It can be seen from the figure that after the impact, the composite material did not undergo obvious deformation and the surface remained intact, indicating that the composite material has strong impact resistance.

[0073] Table 1 also shows the flexural strength and hardness of the composite material, which has high strength and toughness, indicating that the overall mechanical properties of the composite material are good.

[0074] Comparative Example 1

[0075] The difference between Comparative Example 1 and Example 1 is that the densified surface layer is based on unmodified bismaleimide resin.

[0076] Table 2 Performance test results of the composite material obtained in Comparative Example 1

[0077]

[0078]

[0079] It can be seen from the data in Table 2 that the densified surface layer directly uses unmodified bismaleimide resin as the matrix. Compared with Example 1, the overall density and thermal conductivity of the composite material are slightly reduced, but its mechanical properties are significantly reduced, and the ablation rate is also greatly increased, and the ablation resistance is significantly reduced.

[0080] The composite material obtained in this comparative example was subjected to a low-speed impact test, and the test was carried out in a manner of increasing the drop hammer energy. The results showed that Figure 5 As shown in the figure, when the impact energy is 18J, the composite material undergoes obvious deformation, impact marks appear on the surface, and the impact resistance is significantly reduced.

[0081] Comparative Example 2

[0082] The difference between Comparative Example 2 and Example 1 is that the densified surface layer is based on inorganic particle-modified bismaleimide resin, and the inorganic particle-modified bismaleimide resin is composed of bismaleimide resin, boron carbide and zirconium boride in a mass ratio of 80:30:10.

[0083] Table 3 Performance test results of the composite material obtained in Comparative Example 2

[0084]

[0085] It can be seen from the data in Table 2 that the densified surface layer is based on the inorganic particle-modified bismaleimide resin. Compared with Example 1, the overall density of the composite material has increased to a certain extent, and the thermal conductivity has also been significantly improved, indicating that the presence of inorganic particles makes the interior of the resin denser and has a stronger heat transfer capacity, reduces the thermal insulation performance, and significantly increases the ablation rate.

[0086] The composite material obtained in this comparative example was subjected to a butane flame ablation test. Figure 6 It can be seen that the inorganic particles increase the thermal conductivity and heat transfer capacity of the dense surface layer, which ultimately leads to excessive heat transfer, a high increase in the back temperature, and a significant decrease in the thermal insulation performance of the composite material.

[0087] Example 2

[0088] A quartz fiber reinforced phenolic aerogel composite material with a densified surface layer comprises a densified surface layer and a lightweight inner layer; the densified surface layer uses polycarbosilane modified bismaleimide resin as a matrix and quartz fiber woven fabric as a reinforcement; the lightweight inner layer uses phenolic aerogel as a matrix and quartz fiber needle felt as a reinforcement.

[0089] Among them: the polycarbosilane modified bismaleimide resin is composed of bismaleimide resin, polycarbosilane and silane coupling agent in a mass ratio of 100:25:3; the quartz fiber woven fabric is a 2.5D woven fabric with a warp density of 11 yarns / cm, a weft density of 11 yarns / cm, and a thickness of 1mm; the density of the quartz fiber needle felt is 0.3g / cm 3 , thickness is 29mm.

[0090] The method for preparing the composite material comprises the following steps:

[0091] 1) Connect the quartz fiber woven fabric and the quartz fiber needle felt by needle punching, and the needle punching density is 28 needles / cm 2 , forming a connected fiber preform;

[0092] 2) Mixing polycarbosilane with anhydrous ethanol and adding the mixture to bismaleimide resin, wherein the mass ratio of bismaleimide resin to anhydrous ethanol is 100:25, stirring at a rate of 700 r / min for 15 min, and then ultrasonically dispersing the mixture for 20 min, then adding a silane coupling agent, stirring the mixture at a rate of 500 r / min for 1 h, and then heating the mixture to 85° C. and keeping the mixture for 2 h to accelerate the volatilization of ethanol, so that the residual mass of the anhydrous ethanol does not exceed 15% of the sum of the mass of the polycarbosilane and the bismaleimide resin, and then preparing a polycarbosilane-modified bismaleimide resin film with a thickness of 1 mm by a calendering method;

[0093] 3) Covering the surface of the quartz fiber woven fabric of the fiber preform with a polycarbosilane-modified bismaleimide resin film, then placing it in a vacuum bag and evacuating it, closing the vacuum valve and sealing it after the vacuum degree reaches 0.095 MPa, placing it in an oven, heating it to 150°C in the oven and keeping it warm for 2 hours to make the polycarbosilane-modified bismaleimide resin film melt-infiltrate into the quartz fiber woven fabric, and then using a three-stage gradient temperature rise curing method, the three-stage temperatures are 175°C, 205°C, and 225°C, respectively, and the insulation time for each stage is 3 hours. After the curing is completed, take it out, put it into a tubular atmosphere furnace, pass nitrogen (ventilation rate is 20 ml / min), and heat it to 900°C at a rate of 6°C / min for 20 minutes to obtain a fiber preform with a densified surface layer;

[0094] 4) mixing the phenolic resin with anhydrous ethanol, heating to 60° C. to dissolve for 2 h, and then adding hexamethylenetetramine to obtain a phenolic aerogel precursor solution; wherein the mass ratio of the linear phenolic resin, anhydrous ethanol, and hexamethylenetetramine is 100:30:15;

[0095] 5) placing the fiber preform with a densified surface layer into a mold, transferring the phenolic aerogel precursor solution from the surface of the quartz fiber needle felt of the fiber preform inward through a resin transfer molding process, so that the phenolic aerogel precursor solution infiltrates the quartz fiber needle felt, and then using an air compressor to pressurize the mold with a pressure of 0.3 MPa. After the pressing is completed, heating to 100° C. and keeping warm for 36 hours, demolding, taking out and drying naturally for 36 hours, to obtain a quartz fiber reinforced phenolic aerogel composite material with a densified surface layer.

[0096] Table 4 Performance test results of the composite material obtained in Example 2

[0097]

[0098] Example 3

[0099] A quartz fiber reinforced phenolic aerogel composite material with a densified surface layer comprises a densified surface layer and a lightweight inner layer; the densified surface layer uses polycarbosilane modified bismaleimide resin as a matrix and quartz fiber woven fabric as a reinforcement; the lightweight inner layer uses phenolic aerogel as a matrix and quartz fiber needle felt as a reinforcement.

[0100] Among them: the polycarbosilane modified bismaleimide resin is composed of bismaleimide resin, polycarbosilane and silane coupling agent in a mass ratio of 100:35:5; the quartz fiber woven fabric is a 2.5D woven fabric with a warp density of 13 yarns / cm, a weft density of 11 yarns / cm, and a thickness of 3mm; the density of the quartz fiber needle felt is 0.4g / cm 3 , thickness is 27mm.

[0101] The method for preparing the composite material comprises the following steps:

[0102] 1) Connect the quartz fiber woven fabric and the quartz fiber needle felt by needle punching, and the needle punching density is 35 needles / cm 2 , forming a connected fiber preform;

[0103] 2) Mixing polycarbosilane with anhydrous ethanol and adding the mixture to bismaleimide resin, wherein the mass ratio of bismaleimide resin to anhydrous ethanol is 100:20, stirring at a rate of 900 r / min for 10 min, and then ultrasonically dispersing the mixture for 20 min, then adding a silane coupling agent, stirring at a rate of 900 r / min for 2 h, and then heating to 90° C. and keeping the mixture for 2.5 h to accelerate the volatilization of ethanol, so that the residual mass of anhydrous ethanol does not exceed 15% of the sum of the mass of polycarbosilane and bismaleimide resin, and then using a calendering method to prepare a polycarbosilane-modified bismaleimide resin film with a thickness of 3 mm;

[0104] 3) Covering the surface of the quartz fiber woven fabric of the fiber preform with a polycarbosilane-modified bismaleimide resin film, then placing it in a vacuum bag and evacuating it, closing the vacuum valve and sealing it after the vacuum degree reaches 0.099 MPa, placing it in an oven, heating it to 150°C in the oven and keeping it warm for 3 hours to make the polycarbosilane-modified bismaleimide resin film melt-infiltrate into the quartz fiber woven fabric, and then using a three-stage gradient temperature rise curing method, the three-stage temperatures are 185°C, 215°C, and 235°C, respectively, and the insulation time for each stage is 1.5 hours. After the curing is completed, take it out, put it into a tubular atmosphere furnace, pass nitrogen (ventilation rate is 40 ml / min), and heat it to 1000°C at a rate of 8°C / min for 15 minutes to obtain a fiber preform with a densified surface layer;

[0105] 4) mixing phenolic resin and anhydrous ethanol, heating to 75° C. to dissolve for 1 hour, and then adding hexamethylenetetramine to prepare a phenolic aerogel precursor solution; wherein the mass ratio of the linear phenolic resin, anhydrous ethanol, and hexamethylenetetramine is 100:40:12;

[0106] 5) placing the fiber preform with a densified surface layer into a mold, transferring the phenolic aerogel precursor solution from the surface of the quartz fiber needle felt of the fiber preform inward through a resin transfer molding process, so that the phenolic aerogel precursor solution infiltrates the quartz fiber needle felt, and then using an air compressor to pressurize the mold with a pressure of 0.45 MPa. After the pressing is completed, heating to 90° C. and keeping warm for 24 hours, demolding, taking out and drying naturally for 36 hours, to obtain a quartz fiber reinforced phenolic aerogel composite material with a densified surface layer.

[0107] Table 5 Performance test results of the composite material obtained in Example 3

[0108]

[0109] The above embodiments are merely examples for clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above descriptions. It is not necessary and impossible to list all the implementation methods here, and the obvious changes or modifications derived therefrom are still within the protection scope of the invention.

Claims

1. A quartz fiber reinforced phenolic aerogel composite material with a densified surface layer, characterized in that: It comprises a densified surface layer and a light inner layer; the densified surface layer is based on polycarbosilane-modified bismaleimide resin and reinforced by quartz fiber woven fabric, and the polycarbosilane-modified bismaleimide resin is composed of bismaleimide resin, polycarbosilane and silane coupling agent; the light inner layer is based on phenolic aerogel and reinforced by quartz fiber needle felt.

2. The quartz fiber reinforced phenolic aerogel composite material with a densified surface layer according to claim 1, characterized in that: In the polycarbosilane-modified bismaleimide resin, the mass ratio of bismaleimide resin, polycarbosilane and silane coupling agent is 100:(5-35):(0.3-5).

3. The quartz fiber reinforced phenolic aerogel composite material with a densified surface layer according to claim 1, characterized in that: The polycarbosilane is liquid polycarbosilane, and its number average molecular weight is 1000-2000; the solid content of the bismaleimide resin is 75-95%; and the silane coupling agent is gamma-aminopropyltriethoxysilane.

4. The quartz fiber reinforced phenolic aerogel composite material with a densified surface layer according to claim 1, characterized in that: The quartz fiber woven fabric is a 2.5D woven fabric with a warp density of 11 to 13 yarns / cm, a weft density of 9 to 11 yarns / cm, and a thickness of 1 to 3 mm; the density of the quartz fiber needle felt is 0.2 to 0.5 g / cm 3 , thickness is 9~29mm.

5. The quartz fiber reinforced phenolic aerogel composite material with a densified surface layer according to claim 1, characterized in that: The volume density of the composite material is 0.3-0.7 g / cm 3 The room temperature thermal conductivity is 0.07-0.11 W / m·K, the bending strength is 9-13 MPa, and the Shore hardness is 94-100 HA.

6. A method for preparing a quartz fiber reinforced phenolic aerogel composite material having a densified surface layer as claimed in any one of claims 1 to 5, characterized in that: The following steps are involved: 1) connecting the quartz fiber woven fabric and the quartz fiber needle felt by needle punching to form a connected fiber preform; 2) Mix polycarbosilane and anhydrous ethanol and add them to bismaleimide resin, stir first and then disperse by ultrasonic, then add silane coupling agent, continue stirring and heating to volatilize the anhydrous ethanol. Then use calendering method to prepare polycarbosilane modified bismaleimide resin film of a certain thickness; 3) Covering the surface of the quartz fiber woven fabric of the fiber preform with a polycarbosilane-modified bismaleimide resin film, then placing the preform in a vacuum bag, evacuating the bag, and sealing the bag, heating the bag to melt-infiltrate the polycarbosilane-modified bismaleimide resin film into the quartz fiber woven fabric, then heating the bag to cure the preform, taking the bag out, performing a heat treatment in an inert atmosphere, and cooling the bag to room temperature to obtain a fiber preform having a densified surface layer; 4) mixing phenolic resin with anhydrous ethanol, heating to dissolve, and then adding hexamethylenetetramine to obtain a phenolic aerogel precursor solution; 5) placing the fiber preform with a densified surface layer into a mold, transferring the phenolic aerogel precursor solution from the surface of the quartz fiber needle felt of the fiber preform inward through a resin transfer molding process, so that the phenolic aerogel precursor solution infiltrates the quartz fiber needle felt, and then applying pressure into the mold, heating and heat preservation, demolding, taking out and drying, to obtain a quartz fiber reinforced phenolic aerogel composite material with a densified surface layer.

7. The method for preparing the quartz fiber reinforced phenolic aerogel composite material with a densified surface layer according to claim 6, characterized in that: In step 2), the stirring rate is 500-1000 r / min, the stirring time before the addition of the silane coupling agent is 10-20 min, the ultrasonic dispersion time is 5-20 min, and the stirring time after the addition of the silane coupling agent is 0.5-2 h; the heating temperature is 80-90° C., and the heating time is 2-4 h, until the residual mass of anhydrous ethanol does not exceed 15% of the sum of the mass of polycarbosilane and bismaleimide resin; the thickness of the polycarbosilane-modified bismaleimide resin film is the same as the thickness of the quartz fiber woven fabric.

8. The method for preparing the quartz fiber reinforced phenolic aerogel composite material with a densified surface layer according to claim 6, characterized in that: In step 3), the vacuum degree of the vacuum bag after evacuation is 0.09-0.1MPa; the infiltration temperature is 140-150°C, and the infiltration time is 2-6h; the curing adopts three-stage gradient temperature rising curing, the temperature of the first stage is 175-185°C, the temperature of the second stage is 205-215°C, and the temperature of the third stage is 225-235°C, and the insulation time of each stage is 1-3h; the temperature of the heat treatment is 900-1000°C, the heating rate is 2-10°C / min, and the treatment time is 10-30min.

9. The method for preparing the quartz fiber reinforced phenolic aerogel composite material with a densified surface layer according to claim 6, characterized in that: In step 4), the mass ratio of the phenolic resin, anhydrous ethanol and hexamethylenetetramine is 100:(10-60):(10-20); the phenolic resin is a linear phenolic resin with a number average molecular weight of 300-800.

10. The method for preparing the quartz fiber reinforced phenolic aerogel composite material with a densified surface layer according to claim 6, characterized in that: In step 5), an air compressor is used to inject a pressure of 0.3 to 0.5 MPa into the mold, the heating temperature is 90 to 100° C., and the insulation time is 24 to 48 hours.

Citation Information

Patent Citations

  • Thermal-insulating anti-scouring heat shielding layer and preparation method thereof

    CN109367151A

  • Low-density high-temperature-resistant heat-prevention and heat-insulation composite material and preparation method thereof

    CN114311869A

  • Flexible phenolic aldehyde / silicon composite aerogel ablation thermal protection composite material and preparation method thereof

    CN117756445A

  • Production of fiber reinforced composite material

    JP1993070227A

  • Methods for manufacturing coated composite materials

    US20230075051A1

Cited By

  • Organic-inorganic hybrid thermal protection material resistant to ablation of discrete interval fuel gas as well as preparation method and application of organic-inorganic hybrid thermal protection material

    CN119928349A